Bi-Level Optimization Model for Calculation of LMP Intervals Considering the Joint Uncertainty of Wind Power and Demand - Pham, Nang Van (Old Journal, 2018)
In the electricity market operation, electricity prices or Locational Marginal Prices (LMP) vary according to both electric demand and the penetration level of the wind power. The variable domain identification of LMP plays a very important role for market participants to assess and mitigate the risk on account of the combined uncertainty of wind power and demand. Traditionally, the Monte Carlo simulation (MCS) method can be used in order to determine the variable intervals of LMP. However, in this paper, author deploys a bi-level optimization model to calculate the upper and lower bounds of LMP when considering the combined uncertainty of wind power generation and demand. The objective function of the upper-level optimization problem is to maximize (or minimize) LMP at a node whereas the objective function of the lower-level optimization problems is to calculate the optimal power generation of the units participating in supplying the load.